The Secret Seven 1 - Blyton, Enid; Brook, George (Hodder Children's London, 2009)
CLASSIC FICTION. Meet Peter, Janet and Jack, Barbara, Pam, Colin and George. Together they are The Secret Seven - ready to solve any mystery, any time! Book 1: The Secret Seven It's their first adventure and the Secret Seven super-sleuths are already on the trail of a mystery! The gang are dressed in disguise, following a lead to a spooky old house in the snow ... Book 2: Secret Seven Adventure When a priceless pearl necklace goes missing the Secret Seven are first off the mark to catch the thief! Why? Because they saw him making his escape! Now all they have to do is find the necklace ... Book 3: Well Done, Secret Seven The Secret Seven have a new meeting place - a treehouse! But someone else is using it too. The gang are furious, but then they learn the intruder is in big trouble and needs their help. Can the Seven come to the rescue ...? Ages 7+